2021
DOI: 10.1186/s12933-021-01296-5
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end-products, measured as skin autofluorescence, associate with vascular stiffness in diabetic, pre-diabetic and normoglycemic individuals: a cross-sectional study

Abstract: Background Advanced glycation end-products are proteins that become glycated after contact with sugars and are implicated in endothelial dysfunction and arterial stiffening. We aimed to investigate the relationships between advanced glycation end-products, measured as skin autofluorescence, and vascular stiffness in various glycemic strata. Methods We performed a cross-sectional analysis within the European Prospective Investigation into Cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…A significantly increased burden of AGEs was described in aging and age-related diseases (ARDs), primarily in diabetes mellitus [ 2 , 4 ], and their levels, measured using skin autofluorescence, were associated with a significant increase in the incidence of major adverse cardiovascular events (MACE) in a multitude of chronic conditions, including heart failure [ 5 ], type 2 diabetes [ 6 ], and end-stage renal disease [ 7 ]. The contribution of AGEs in fostering endothelial dysfunction and exacerbating atherosclerosis has been confirmed by their robust association with non-invasive measures of arterial stiffness, which is more pronounced in men and younger individuals [ 8 ]. The membrane-bound RAGE (FL-RAGE) is a pattern recognition receptor that recognizes AGEs and several other ligands, some of which act as damage-associated molecular patterns (DAMPS) and pathogen-associated molecular patterns (PAMPs) [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A significantly increased burden of AGEs was described in aging and age-related diseases (ARDs), primarily in diabetes mellitus [ 2 , 4 ], and their levels, measured using skin autofluorescence, were associated with a significant increase in the incidence of major adverse cardiovascular events (MACE) in a multitude of chronic conditions, including heart failure [ 5 ], type 2 diabetes [ 6 ], and end-stage renal disease [ 7 ]. The contribution of AGEs in fostering endothelial dysfunction and exacerbating atherosclerosis has been confirmed by their robust association with non-invasive measures of arterial stiffness, which is more pronounced in men and younger individuals [ 8 ]. The membrane-bound RAGE (FL-RAGE) is a pattern recognition receptor that recognizes AGEs and several other ligands, some of which act as damage-associated molecular patterns (DAMPS) and pathogen-associated molecular patterns (PAMPs) [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a subset of patients of the European Prospective Investigation into Cancer and Nutrition (EPIC)-Potsdam cohort (EPIC-DZD), AGEs were measured independent of diabetes status and vascular stiffness. Skin autofluorescence was positively associated with markers of vascular stiffness, such as pulse wave velocity and augmentation index in diabetic patients, and the ankle-brachial index was inversely associated with skin autofluorescence across all sex, age, and glycaemia strata [ 92 ].…”
Section: Role Of Mgo In Selected Vascular Diseasesmentioning
confidence: 99%
“…SAF is strongly correlated with pulse wave velocity, brachial and aortic augmentation indices, and ankle-brachial index, all of them markers of arterial stiffness [ 72 ]. Birukov et al [ 84 ] recently investigated the relationships between SAF and vascular stiffness in a large study performed in diabetic and non-diabetic populations. These authors concluded that SAF might be involved in vascular stiffening independently of cardiometabolic risk factors, and it could be a rapid and non-invasive method for the assessment of macrovascular disease progression across all glycemic strata [ 84 ].…”
Section: Saf and Diabetic Macrovascular Complicationsmentioning
confidence: 99%
“…Birukov et al [ 84 ] recently investigated the relationships between SAF and vascular stiffness in a large study performed in diabetic and non-diabetic populations. These authors concluded that SAF might be involved in vascular stiffening independently of cardiometabolic risk factors, and it could be a rapid and non-invasive method for the assessment of macrovascular disease progression across all glycemic strata [ 84 ]. However, Osawa et al [ 82 ], in a smaller study including only subjects with type 2 diabetes, showed that SAF was significantly associated with C-IMT and pulse wave velocity (PWv), but it was not an independent determinant of C-IMT and PWv after adjustment for confounders [ 82 ].…”
Section: Saf and Diabetic Macrovascular Complicationsmentioning
confidence: 99%